DNA hydrolysing IgG catalytic antibodies: an emerging link between psychoses and autoimmunity - Rajendran Ramesh (Nature Portfolio, 2021)
Abstract It is not uncommon to observe autoimmune comorbidities in a significant subset of patients with psychotic disorders, namely schizophrenia (SCZ) and bipolar disorder (BPD). To understand the autoimmune basis, the DNA abyzme activity mediated by serum polyclonal IgG Abs were examined in psychoses patients, quantitatively, by an in-house optimized DNase assay. A similar activity exhibited by IgG Abs from neuropsychiatric-systemic lupus erythematosus (NP-SLE) patients was used as a comparator. Our data revealed that the IgG DNase activity of SCZ was close to that of NP-SLE and it was twofold higher than the healthy controls. Interestingly, the association between DNase activity with PANSS (positive, general and total scores) and MADRS were noted in a subgroup of SCZ and BPD patients, respectively. In our study group, the levels of IL-6 and total IgG in BPD patients were higher than SCZ and healthy controls, indicating a relatively inflammatory nature in BPD, while autoimmune comorbidity was mainly observed in SCZ patients.